FACTORS AFFECTING RICE RICE PRODUCTIVITY IN GAMPONG KUTA MEULIGOE, SAWANG DISTRICT, ACEH UTARA REGENCY - Irwanda Irwanda; Mawardati Mawardati; Rita Ariani (Jurnal Mahasiswa Agribisnis, 2022)
The research was conducted in Kuta Meuligoe village, Sawang subdistrict, North Aceh regency from September to October 2018. This study aims to determine the factors that affect the productivity of paddy rice fields. The analysis method used Cobb-Douglas production function analysis. The result describes the relationships between variables through hypothesis testing research on factors that affect the productivity of rice. In this study used primary data (data obtained from respondents) and secondary data (data acquired from the library, journal and related institutions). equation of linear regression used is multiplied by test hypothesis. Test are F Test and T as well as testing the assumptions of normality. Classical multicollinearity and heteroscedasticity. Variables that have significant effect are urea fertilizer and fertilizer shortages